A Comparative Analysis of Factors Contributing to Relapse in Alcohol and Opioid Dependence Among Patients Admitted to Selected Hospitals in Ludhiana, Punjab. - Amandeep Kaur; Satwant Kaur (International Journal of Evidence Based Nursing And Practices, 2024)
Introduction: Substance abuse involves the dangerous or detrimental use of psychoactive substances, such as alcohol and illegal drugs. The use of these substances can result in dependence syndrome, which encompasses a range of behavioral, cognitive, and physiological effects that arise from ongoing substance use. Objectives: This study was carried out to examine the factors linked to relapse in alcohol and opioid dependence among patients admitted to selected hospitals in Ludhiana, Punjab. Conceptual Framework: was based on health belief model Methodology: A comparative study was conducted on 100 samples of patients alcohol dependence (50) and opioid (50) who were selected by purposive sampling technique. Self-structured checklist was used that had four sections. Section 1 was to obtain the socio demographic data from respondents. Section 2 consisted of five sub factoreach had 10 items related to that factor and minimum score was 00 and maximum was 10. Results: In opioid patient’s majority 42 (84%) had severe effect followed by 08 (16%) had moderate and none had mild effect of all factors. In alcoholic patients majority 34 (68%) had severe effect followed by 16(32%) had moderate and none had mild effect of all factors. Personal and family factor,psychological factors were almost the main reason that effect both opioid and alcoholic patient. There was statistically non-significant relationship of age and marital status and residence area of associated with relapse in alcohol dependence with selected socio-demographic profile whereas age, family type and area of residence found non-significant in opioid dependence patients. Conclusion: Emotional factor, Personal factor, social factors were almost the main reason that effect both opioid and alcoholic patient. There was statistically non-significant relationship of age and marital status and residence area of associated with relapse in alcohol & opioid dependence patients.
Keywords: Relapse; alcohol dependence; opioid; patient